Linear polysialoside outperforms dendritic analogs for inhibition of influenza virus infection in vitro and in vivo. (September 2017) - Bhatia, Sumati; Lauster, Daniel; Bardua, Markus; Ludwig, Kai; Angioletti-Uberti, Stefano; Popp, Nicole; Hoffmann, Ute; Paulus, Florian; Budt, Matthias; Stadtmüller, Marlena; Wolff, Thorsten; Hamann, Alf; et al.
Abstract: Inhibition of influenza A virus infection by multivalent sialic acid inhibitors preventing viral hemagglutinin binding to host cells of the respiratory tract is a promising strategy. However, optimal geometry and optimal ligand presentation on multivalent scaffolds for efficient inhibition both in vitro and in vivo application are still unclear. Here, by comparing linear and dendritic polyglycerol sialosides (LPGSA and dPGSA) we identified architectural requirements and optimal ligand densities for an efficient multivalent inhibitor of influenza virus A/X31/1 (H3N2). Due to its large volume, the LPGSA at optimal ligand density sterically shielded the virus significantly better than the dendritic analog. A statistical mechanics model rationalizes the relevance of ligand density, morphology, and the size of multivalent scaffolds for the potential to inhibit virus-cell binding. Optimized LPGSA inhibited virus infection at IC50 in the low nanomolar nanoparticle concentration range and also showed potent antiviral activity against two avian influenza strains A/Mallard/439/2004 (H3N2) and A/turkey/Italy/472/1999 (H7N1) post infection. I n vivo application of inhibitors clearly confirmed the higher inhibition potential of linear multivalent scaffolds to prevent infection. The optimized LPGSA did not show any acute toxicity, and was much more potent than the neuraminidase inhibitor oseltamivir carboxylate in vivo . Combined application of the LPGSA and oseltamivir carboxylate revealed a synergistic inhibitory effect and successfully prevented influenza virus infection in mice. Graphical abstract: